Advances in Understanding of Structural Reorganization in the Hypothalamic Neurosecretory System - Miyata, Seiji (Frontiers in Endocrinology, 2017)
The hypothalamic neurosecretory system synthesizes neuropeptides in hypothalamic nuclei and releases them from axonal terminals into the circulation in the neurohypophysis (NH) and median eminence (ME). This system plays a crucial role in regulating body fluid homeostasis and social behaviors as well as reproduction, growth, metabolism, and stress responses, and activity-dependent structural reorganization has been reported. Current knowledge on dynamic structural reorganization in the NH and ME, in which the axonal terminals of neurosecretory neurons directly contact the basement membrane (BM) of a fenestrated vasculature, is discussed herein. Glial cells, pituicytes in the NH and tanycytes in the ME, engulf axonal terminals and interpose their cellular processes between axonal terminals and the BM when hormonal demands are low. Increasing demands for neurosecretion result in the retraction of the cellular processes of glial cells from axonal terminals and the BM, permitting increased neuro-vascular contact. The shape conversion of pituicytes and tanycytes is mediated by neurotransmitters and sex steroid hormones, respectively. The NH and ME have a rough vascular BM profile of wide perivascular spaces and specialized extension structures called “perivascular protrusions”. Perivascular protrusions, the insides of which are occupied by the cellular processes of vascular mural cells pericytes, contribute to increasing neuro-vascular contact and, thus, the efficient diffusion of hypothalamic neuropeptides. A chronic physiological stimulation has been shown to increase perivascular protrusions via the shape conversion of pericytes and the profile of the vascular surface. Continuous angiogenesis occurs in the NH and ME of healthy normal adult rodents depending on the signaling of vascular endothelial growth factor (VEGF). The inhibition of VEGF signaling suppresses the proliferation of endothelial cells and promotes their apoptosis, which results in decreases in the population of endothelial cells and axonal terminals. Pituicytes and tanycytes are continuously replaced by the proliferation and differentiation of stem/progenitor cells, which may be regulated by matching those of endothelial cells and axonal terminals. In conclusion, structural reorganization in the NH and ME is caused by the activity-dependent shape conversion of glial cells and vascular mural cells as well as the proliferation of endothelial and glial cells by angiogenesis and gliogenesis, respectively.